Systematic Literature Review: Application of Whole Language Approach to Improve Indonesian Language Learning Outcomes of Elementary School Students - Safira, Ansella; Firmansah, Deri; Afriyadi, Muhammad Muchsin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The Whole Language approach has been widely applied in Indonesian language learning, but there is still a gap in understanding its effectiveness, especially in elementary schools. This study aims to examine the application and effectiveness of Whole Language in improving Indonesian learning outcomes in elementary school students. This study uses Systematic Literature Review (SLR). The article selection process was carried out through searches in indexed journal databases such as Google Scholar, DOAJ, and Garuda with the keywords